PENERAPAN HUKUM ANTARA BANK SYARIAH DAN NASABAH DALAM AKAD PEMBIAYAAN MURABAHAH BIL WAKALAH YANG OBJEKNYA TANAH DENGAN RUMAH - Mentari Fajarina (STIS Darussalam Bermi, 2024)
The purpose of the study is to analyze the concept of murabahah on the one hand whose technical guidelines are determined by the National Sharia Council which refers to Islamic sharia and on the other hand must also be in accordance with positive law to obtain protection and legal certainty, then sharia law and positive law should be followed consistently by Islamic banking in providing murabahah financing whose contracts. First, according to Law Number 21 of 2008 concerning Islamic Banking in Article 1 number 7, Islamic Banks are Banks that carry out their business activities based on Sharia Principles and according to their types consist of Islamic Commercial Banks and Islamic People's Financing Banks. It is emphasized that the Sharia Principle according to Law Number 21 of 2008 concerning Islamic Banking in Article 1 number 12 is the principle of Islamic law in banking activities based on fatwas issued by institutions that have the authority to determine fatwas in the field of sharia. From the financing of murabahah agreements in BPR Syariah in terms of determining profits in accordance with sharia principles because the National Sharia Council allows that murabahah sales and purchases transactions, either cash or installments, with the terms and conditions can be met. In the murabahah agreement in BPR Syariah, partnerships are always prioritized, transparent so that customers can accept the agreement or agreement that has been agreed upon with the note that both parties agree must be based on Islamic law. In BPR Syariah, customers are allowed to negotiate earlier for the purchase of goods either on credit or paid in cash.